Physicochemical characterization and sensory enhancement of cold plasma treated black whole wheat flour - Teng Zhang; Ling He; Meng Zhang; Hao Jiang (Scientific Reports)
Abstract This study examined the effects of cold plasma (CP) treatment on the physicochemical properties and sensory quality of black whole wheat flour (BWWF). Various factors including nutrient composition, color, amino acids, aroma, particle size, microstructure, antioxidant activity, and water migration were analyzed before and after CP treatment. The findings revealed that CP treatment had a minimal impact on the baseline nutrient composition of BWWF, but significantly improved its free amino acid profile, enhancing its nutritional value. The treated BWWF had an improved surface color, appeared brighter and yellower, and gave off a pleasant mellow aroma, while removing unpleasant flavor. The total phenolic content of BWWF increased while the flavonoid and anthocyanin content decreased after the treatment. CP-treated BWWF underwent aggregation cross-linking in the microstructure, and the content of bound water decreased, but the stability increased. In conclusion, CP treatment had great potential to improve the physicochemical properties and sensory quality of BWWF.